Capitan Pepe - Empaynado, Carlos; Estrada, Joseph; Bautista, Perla; Delgado, Lauro; Gallardo, Cesar; Cinema One Originals (Firm). ([Place of production not identified] Emar Pictures, 1969)
Is there a qualification to lead? Jose a.k.a. Pepe (Joseph Estrada) did prove to the people in their barrio that the real concern and love to your constituent is the key to a good public service. Capitan Pepe is a story of dirty and funny side of politics even in the small barrio and it was even made exciting when romance tried to find its place despite the conflict.--https://www.imdb.com/title/tt0411209/plotsummary?ref_=tt_ov_pl
Produced by Joseph Estrada; music by Ernani Cuenco; cinematography by Luis Chiong.
Joseph Estrada, Perla Bautista, Lauro Delgado.
DVD
In Tagalog
Keywords: Drama